Pathological and Microbiological Analysis of Cerebrospinal Fluid in Bacterial Meningitis - Ramesh S T; Girish Babu R J (Tropical Journal of Pathology and Microbiology, 2016)
Background: Meningitis is a life threatening infection with incidences increasing in adults and children. CSF analysis is a key tool to diagnose and differentiate between bacterial, viral, tubercular and fungal meningitis. Identifying the causative bacterial organisms is important to guide antimicrobial therapy. Aims &objectives: The present study was undertaken to analyze CSF parameters and to determine causative organisms of meningeal infection and also to find out their antibiotic susceptibility pattern.Settings and design: Cross sectional study.Methods and Materials: The study includes 100 clinically suspected cases of meningitis. Pathological and Biochemical analysis was done. Bacterial pathogens were identified by conventional methods of culture with sensitivity pattern.Results: Out of 100 cases, 30 cases showed total count >1000cells/ul with neutrophil predominance. 25 cases shows culture growth, with Escherichia coli as predominant organism isolated followed by Streptococcus pneumonia. Imipenem showed 100% sensitivity followed by Pipercillin/Tazobactum 90%.Conclusion: Our results of CSF fluid analysis revealed a total count of >1000 cells /ul with neutrophil predominance. Escherichia coli was the predominant organism isolated. Imipenem showed 100% sensitivity.